Q. Solve the system of equations by elimination.2x−3y−z=−11−x−y−z=−11x−2y−2z=−10
Eliminate x: Add the first and second equations to eliminate x.(2x−3y−z)+(−x−y−z)=−11+(−11)2x−x−3y−y−z−z=−22x−4y−2z=−22
Prepare for elimination: Multiply the second equation by 2 to prepare for elimination with the third equation.2(−x−y−z)=2(−11)−2x−2y−2z=−22
Eliminate x: Add the modified second equation and the third equation to eliminate x.(−2x−2y−2z)+(x−2y−2z)=−22+(−10)−2x+x−2y−2y−2z−2z=−32−x−4y−4z=−32
Simplify equation: Divide the last equation by −1 to simplify.−1−x−−14y−−14z=−1−32x+4y+4z=32
Eliminate y and z: Now we have two equations with x, y, and z:x−4y−2z=−22x+4y+4z=32Add these two equations to eliminate y and z.(x−4y−2z)+(x+4y+4z)=−22+32x+x−4y+4y−2z+4z=102x+2z=10
Solve for x: Divide the last equation by 2 to solve for x.22x+22z=210x+z=5
Solve for y: Substitute x+z=5 into x−4y−2z=−22 to solve for y. (5−z)−4y−2z=−22 5−z−4y−2z=−22 5−4y−3z=−22
Substitute x+z=5: Isolate the term with y. −4y=−22−5+3z −4y=−27+3z
Solve for z: Divide by −4 to solve for y.y=−4−27+3zy=427−(43)z
Solve for x: Substitute x+z=5 into x+4y+4z=32 to solve for y. (5−z)+4y+4z=32 5+4y+3z=32
Solve for z: Isolate the term with y.4y=32−5−3z4y=27−3z
Solve for z: Isolate the term with y.4y=32−5−3z4y=27−3zDivide by 4 to solve for y.y=427−3zy=427−43z
Solve for z: Isolate the term with y.4y=32−5−3z4y=27−3zDivide by 4 to solve for y.y=427−3zy=427−43zWe have two expressions for y that must be equal:427−43z=427−43zThis is always true for all z, so we need to find a specific value for z using another equation.
Solve for z: Isolate the term with y. 4y=32−5−3z 4y=27−3zDivide by 4 to solve for y. y=427−3z y=427−43zWe have two expressions for y that must be equal: 427−43z=427−43z This is always true for all z, so we need to find a specific value for z using another equation.Substitute y=427−43z into y3 to solve for z. y5 y6 y7
Solve for z: Isolate the term with y.4y=32−5−3z4y=27−3zDivide by 4 to solve for y.y=427−3zy=427−43zWe have two expressions for y that must be equal:427−43z=427−43zThis is always true for all z, so we need to find a specific value for z using another equation.Substitute y=427−43z into x−4y−2z=−22 to solve for z.4y=27−3z14y=27−3z24y=27−3z3We already have 4y=27−3z3, so we need to find a specific value for z using another equation.
Solve for z: Isolate the term with y.4y=32−5−3z4y=27−3zDivide by 4 to solve for y.y=427−3zy=427−43zWe have two expressions for y that must be equal:427−43z=427−43zThis is always true for all z, so we need to find a specific value for z using another equation.Substitute y=427−43z into x−4y−2z=−22 to solve for z.4y=27−3z04y=27−3z14y=27−3z2We already have 4y=27−3z2, so we need to find a specific value for z using another equation.Substitute y=427−43z into 4y=27−3z6 to solve for z.4y=27−3z84y=27−3z9
Solve for z: Isolate the term with y.4y=32−5−3z4y=27−3zDivide by 4 to solve for y.y=427−3zy=427−43zWe have two expressions for y that must be equal:427−43z=427−43zThis is always true for all z, so we need to find a specific value for z using another equation.Substitute y=427−43z into x−4y−2z=−22 to solve for z.x−4(427−43z)−2z=−22x−27+3z−2z=−22x+z=5We already have x+z=5, so we need to find a specific value for z using another equation.Substitute y=427−43z into 4y=27−3z2 to solve for z.4y=27−3z34y=27−3z44y=27−3z5
Solve for z: Isolate the term with y.4y=32−5−3z4y=27−3zDivide by 4 to solve for y.y=427−3zy=427−43zWe have two expressions for y that must be equal:427−43z=427−43zThis is always true for all z, so we need to find a specific value for z using another equation.Substitute y=427−43z into y3 to solve for z.y5y6y7We already have y7, so we need to find a specific value for z using another equation.Substitute y=427−43z into 4y=32−5−3z1 to solve for z.4y=32−5−3z34y=32−5−3z4Multiply all terms by 4 to clear the fraction.4y=32−5−3z64y=32−5−3z7Substitute y7 into 4y=32−5−3z7 to solve for 4y=27−3z0.4y=27−3z14y=27−3z24y=27−3z3
Solve for z: Isolate the term with y.4y=32−5−3z4y=27−3zDivide by 4 to solve for y.y=427−3zy=427−43zWe have two expressions for y that must be equal:427−43z=427−43zThis is always true for all z, so we need to find a specific value for z using another equation.Substitute y=427−43z into x−4y−2z=−22 to solve for z.x−4(427−43z)−2z=−22x−27+3z−2z=−224y=27−3z0We already have 4y=27−3z0, so we need to find a specific value for z using another equation.Substitute y=427−43z into 4y=27−3z3 to solve for z.4y=27−3z44y=27−3z5Multiply all terms by 4 to clear the fraction.4y=27−3z74y=27−3z8Substitute 4y=27−3z0 into 4y=27−3z8 to solve for x.414243Divide by 44 to solve for z.4546
More problems from Solve a system of equations in three variables using elimination